ЎЗБЕК ВА ҚОРАҚАЛПОҚ АДАБИЙ АЛОҚАЛАРИДА МИРТЕМИР ИЖОДИНИНГ ВОСИТАЧИЛИК РОЛИ - Қурамбоева, Г. (SCIENCE and SOCIETY, 2019)
The article deals with the mediating role of Mirtemur in the development of the Uzbek-Karakalpak literary connection, the author analyzes the verses and poems that are is dedicated to the Karakalpak theme, and also deals with the poet’s translations from Karakalpak literature.
Keywords: literary connections; lyrics; literary translation; artistic cycle; poet; writer; national character; epos; literary-artistic